State of the art in composition, fabrication, characterization, and modeling methods of cement-based thermoelectric materials for low-temperature applications. (March 2021) - Liu, Xiaoli; Jani, Ruchita; Orisakwe, Esther; Johnston, Conrad; Chudzinski, Piotr; Qu, Ming; Norton, Brian; Holmes, Niall; Kohanoff, Jorge; Stella, Lorenzo; Yin, Hongxi; Yazawa, Kazuaki
Abstract: The worldwide energy crisis and environmental deterioration are probably humanity's greatest challenges. Thermoelectricity, which allows for the mutual conversion between thermal and electrical energy, has become a promising technology to alleviate this challenge. Increasingly more research focuses on how to fabricate and apply thermoelectric materials for harvesting energy and regulating the indoor thermal environment. However, only a few studies have focused on cementitious materials with thermoelectric potential. Thermoelectric cement is a composite material in which particular additives can enhance the thermoelectric performance of ordinary cement. By potentially replacing traditional construction materials with thermoelectric cement in building applications, electricity could be generated from waste heat, reducing the use of fossil fuels, and supplementing other renewable energy sources like solar and wind. This article presents a review of fundamentals, fabrication, characterization, composition, and performance, as well as modeling methods and opportunities for thermoelectric cement composites. The literature reviewed covers the period from 1998 to 2020 related to thermoelectric cement. It also presents the challenges and problems to overcome for further development and provide future research directions of thermoelectric cement. Highlights: Fabrication, characterization, and performance of TE cement are summarized. Existing studies measured TE properties of cement composites separately. Most TE cement composites exhibit ZT lower than 10 −3 . ZT of graphene and Al-doped ZnO enhanced cement was improved to 10 −2 . Atomistic and macroscale modeling for TE composite materials are reviewed.